Usage of the interval method for solving some inequalities - Grebenečenkaitė, Petrė (Lietuvos matematikos rinkinys, 1998)
A method of intervals helps to solve complex inequality with parameter. This method makes it easier to solve inequality. This method is widely used. It develops the thinking of pupils